2011
DOI: 10.1002/jcop.20460
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood violence and use of verbal aggression, corporal punishment, and physical abuse by a national sample of parents in Israel

Abstract: This study, based on an ecological perspective, examined the relation of perceived neighborhood violence, child misbehavior, parental attitudes to aggressive discipline tactics, and the actual use of aggressive discipline tactics. Research questions were: To what extent is perceived neighborhood violence associated with aggressive discipline by parents? What is the mechanism through which perceived neighborhood violence is linked to aggressive discipline? Data were obtained from a stratified probability sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Furthermore, there were no significant additive or multiplicative effects of child age or sex on parenting perceptions of self‐reported behaviour. It is possible that gender and age effects identified in other studies may not apply in these highly stressed communities, a finding in line with other studies that find that high levels of community violence increase the likelihood of violent parenting (Winstock & Straus, 2011). Future studies should investigate the conditions under which these age and gender effects apply.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, there were no significant additive or multiplicative effects of child age or sex on parenting perceptions of self‐reported behaviour. It is possible that gender and age effects identified in other studies may not apply in these highly stressed communities, a finding in line with other studies that find that high levels of community violence increase the likelihood of violent parenting (Winstock & Straus, 2011). Future studies should investigate the conditions under which these age and gender effects apply.…”
Section: Discussionsupporting
confidence: 81%
“…Exposure to similar risk and protective factors. This is especially likely in the case of marital dyads who live in the same neighborhood including violent neighborhoods (Winstok & Straus, 2011) and share many life experiences including stressors such as unemployment.…”
Section: Fundamental Aspects Of Dyadic Relationshipsmentioning
confidence: 99%
“…The importance of parents’ attitudes has been repeatedly demonstrated. For example, Winstok and Straus (2011) found that parents’ approval of “aggressive discipline” (beating and/or physical force) predicts their use of emotional punishment (shouting, scolding, “telling the child off”), physical punishment (spanking, smacking, shaking), and physical abuse (beating, punching, hitting with a stick or belt). Approval and normalization of physical punishment has been found to be a powerful predictor of its use (Ateah & Durrant, 2005; Durrant, Rose-Krasnor, & Broberg, 2003; Vittrup, Holden, & Buck, 2006; Socolar & Stein, 1995).…”
mentioning
confidence: 99%